Mitochondrial toxicity of triclosan on mammalian cells. (2015) - Ajao, Charmaine; Andersson, Maria A.; Teplova, Vera V.; Nagy, Szabolcs; Gahmberg, Carl G.; Andersson, Leif C.; Hautaniemi, Maria; Kakasi, Balazs; Roivainen, Merja; Salkinoja-Salonen, Mirja
Highlights: We show (sub)cellular toxicity of triclosan (TCS) on six types of mammalian cells. 1–5 μg ml −1 TCS induced metabolic acidification and uncoupled respiration. TCS ceased progressive boar sperm motility at 1 μg ml −1 . TCS uncouples ATP synthetase complex V in mitochondrion. TCS caused regression of pancreatic islets to pycnotic cells. Abstract: Effects of triclosan (5-chloro-2′-(2, 4-dichlorophenoxy)phenol) on mammalian cells were investigated using human peripheral blood mono nuclear cells (PBMC), keratinocytes (HaCaT), porcine spermatozoa and kidney tubular epithelial cells (PK-15), murine pancreatic islets (MIN-6) and neuroblastoma cells (MNA) as targets. We show that triclosan (1–10 μg ml −1 ) depolarised the mitochondria, upshifted the rate of glucose consumption in PMBC, HaCaT, PK-15 and MNA, and subsequently induced metabolic acidosis. Triclosan induced a regression of insulin producing pancreatic islets into tiny pycnotic cells and necrotic death. Short exposure to low concentrations of triclosan (30 min, ≤1 μg/ml) paralyzed the high amplitude tail beating and progressive motility of spermatozoa, within 30 min exposure, depolarized the spermatozoan mitochondria and hyperpolarised the acrosome region of the sperm head and the flagellar fibrous sheath (distal part of the flagellum). Experiments with isolated rat liver mitochondria showed that triclosan impaired oxidative phosphorylation, downshifted ATP synthesis, uncoupled respiration and provoked excessive oxygen uptake. These exposure concentrations are 100–1000 fold lower that those permitted in consumer goods. The mitochondriotoxic mechanism of triclosan differs from that of valinomycin, cereulide and the enniatins by not involving potassium ionophoric activity.